Physical Education, Sports, and Health as a Social Space: A Sociological Study of Participation and Social Cohesion in the Learning Process - Nur Istiqamah; Alif Kurniawan; Muh. Adnan Hudain; Alimin Alwi; Fahrizal (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the role of physical education as a social space that fosters student participation and social cohesion in elementary schools. The research was conducted at UPT SD Negeri 179 Inpres Balang using a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and Focus Group Discussion (FGD), and then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that student participation in physical education is not only limited to physical involvement but also includes social interactions, teamwork, decision-making, and peer support. Supporting factors of participation include students’ internal motivation, the role of PE teachers, adequate facilities, and a supportive social environment, while inhibiting factors consist of limited facilities, differences in physical ability, less supportive learning climate, external factors, and lack of parental support. Furthermore, physical education significantly contributes to building social cohesion by enhancing social interactions, fostering solidarity, reducing discrimination, shaping sportive and democratic character, and serving as a medium for conflict resolution. Thus, physical education functions as a strategic instrument to strengthen values of equality, togetherness, and social integration in elementary schools.